Flexible thermal interface material with phase change function and preparation method thereof

By adding aluminum nitride and phase change particles to the organic silicone matrix, flexible thermal interface materials with phase change function are prepared, which solves the problems of poor thermal conductivity and insufficient phase change heat absorption in traditional materials, and achieves efficient thermal conductivity and Phase change absorbs heat, avoiding leakage.

CN119463513APending Publication Date: 2025-02-18CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411617124.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional thermal interface materials have problems such as poor thermal conductivity and insufficient phase change heat absorption in the heat dissipation applications of high-power electronic devices, and are prone to leakage, affecting the heat transfer effect of the material.

Method used

Using organic silicone as the matrix, aluminum nitride and phase change particles were added, and flexible thermal interface materials with phase change function were prepared through high-speed stirring and addition curing reaction.

Benefits of technology

It improves the thermal conductivity and latent heat value of the phase change, inhibits the leakage of paraffin, enhances the flexibility and fit of the material, and reduces the heat transfer thermal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463513A_ABST
    Figure CN119463513A_ABST
Patent Text Reader

Abstract

The invention provides a flexible thermal interface material with a phase change function and a preparation method thereof, and belongs to the field of thermal interface materials, and the flexible thermal interface material with the phase change function comprises the following raw materials: double-end side chain vinyl silicone oil, hydrogen-containing silicone oil, a catalyst, phase change particles and aluminum nitride particles. The flexible organic silica gel is filled with the phase change particles and the aluminum nitride particles, so that the thermal interface material is endowed with a phase change function with a suitable temperature point, the thermal conductivity of the organic silica gel is remarkably improved, and the problems of low thermal conductivity and poor heat absorption capacity of the thermal interface material are effectively solved. The flexible thermal interface material with the phase change function is low in preparation cost and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal interface materials, and relates to a flexible thermal interface material with phase change function and a preparation method thereof. Background Art

[0002] With the rapid development of integration and high power of electronic components, a large amount of heat will accumulate, which will affect the working efficiency and service life of electronic devices. Thermal interface materials can build an effective heat conduction path between electronic devices and heat sinks, reduce thermal resistance, and improve heat dissipation performance. Therefore, it is of great significance to develop thermal interface materials with good heat dissipation performance.

[0003] Traditional thermal interface materials are thermal grease and thermal pads. Thermal grease has good wettability and low contact thermal resistance, and can effectively fill the gap between contact surfaces. However, due to its unstable shape, there is a risk of grease overflowing and contaminating the circuit board, which may cause short circuits and other dangers. Thermal pads are a flexible, compressible elastic material, but they are prone to stress relaxation during use, resulting in increased contact thermal resistance and affecting the thermal conductivity of the material.

[0004] In summary, traditional thermal interface materials have certain limitations and challenges in the heat dissipation applications of some high-power electronic devices. In order to solve these problems, it is necessary to develop new thermal interface materials. We focus on phase-change thermal interface materials with stable morphology. When the electronic device is working, the local temperature gradually rises, and the phase-change thermal interface material changes from solid to liquid, and the solid-solid contact between the upper and lower contact surfaces changes to solid-liquid contact. This process can not only absorb heat, but also enhance the interaction between the phase-change thermal interface material and the contact surface, further reducing the heat transfer thermal resistance.

[0005] Traditional phase change materials are solid-liquid phase change, which can easily lead to leakage during application, thus affecting the heat transfer effect of the material and even damaging electronic devices. Therefore, solving the leakage problem of phase change thermal interface materials is a huge challenge in the development of phase change thermal interface materials. Summary of the invention

[0006] In view of the above problems, the present invention provides a flexible thermal interface material with phase change function and a preparation method thereof. The thermal interface material uses organic silica gel as a matrix and aluminum nitride and phase change particles as fillers to solve the problems of poor thermal conductivity and lack of phase change heat absorption in the thermal interface material.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The present invention provides a flexible thermal interface material with phase change function and a preparation method thereof, comprising the following raw materials in parts by mass: 47.5 parts of double-end side-chain vinyl silicone oil, 2.5 parts of hydrogen-containing silicone oil, 0.1 parts of a catalyst, 57.5 parts of phase change particles and 0-6 parts of aluminum nitride particles, 47.5 parts of the double-end side-chain vinyl silicone oil in parts by mass are weighed and added into a glass beaker, and pre-stirred and dispersed by a high-speed stirrer, and further 57.5 parts of the phase change particles and 0-6 parts of the aluminum nitride particles in parts by mass are weighed and added into the glass beaker, and then the phase change particles are pre-stirred and dispersed by a high-speed stirrer ... The double-end side-chain vinyl silicone oil is stirred for no less than 30 minutes to allow the mixed material to have phase change function and thermal conductivity. Then, 2.5 parts of the hydrogen-containing silicone oil are weighed by weight and added to the double-end side-chain vinyl silicone oil mixture mixed with phase change particles and stirred for 15 minutes. Then, 0.1 parts of the catalyst is weighed by weight and added to the beaker to promote the addition curing reaction between the double-end side-chain vinyl silicone oil and the hydrogen-containing silicone oil. Finally, it is cooled to room temperature to prepare a flexible thermal interface material with phase change function.

[0009] Preferably, the viscosity of the double-end side-chain vinyl silicone oil is preferably 500-700 cst, wherein the vinyl content is preferably 10 mol%, and the volatile matter is ≤1%.

[0010] Preferably, the phase change particles are prepared by high-temperature melt blending of expanded graphite and paraffin in a ratio of 1:20 by mass into a composite phase change material block. Furthermore, the composite phase change material block is crushed and the particles are screened using a high-speed crusher to finally obtain the phase change particles with particle sizes of 0.2-0.45 mm, 0.1-0.2 mm and less than 0.1 mm, respectively. Furthermore, the phase change temperature of the phase change particles is preferably 20-55°C, and the phase change latent heat value of the phase change particles is not less than 207 J / g.

[0011] Preferably, the aluminum nitride particles are hexagonal aluminum nitride particles, wherein the particle size is 1 μm and the specific surface area is 1.5 to 2 m 2 / g.

[0012] The present invention provides a method for preparing a flexible thermal interface material with phase change function, comprising:

[0013] (1) heating paraffin wax at 70° C. until completely melted, heating expanded graphite into the molten paraffin wax, stirring at a speed of 400 r / min for 3 h, cooling to room temperature, and crushing to obtain phase change particles with particle sizes of 0.2 to 0.45 mm, 0.1 to 0.2 mm, and less than 0.1 mm;

[0014] (2) Pour 30 parts of 0.2-0.45 mm, 17.5 parts of 0.1-0.2 mm, 10 parts of phase change particles smaller than 0.1 mm and 0-6 parts of aluminum nitride into 47.5 parts of double-end side chain vinyl silicone oil and stir for 30 min (400 r / min), then continue to add 2.5 parts of hydrogenated silicone oil and stir for 15 min (400 r / min);

[0015] (3) adding 0.1 parts of platinum catalyst dropwise and continuing stirring at 400 r / min for 50 s;

[0016] (4) Before the prepared mixture material is completely cured, the mixture is subjected to vacuum degassing and accelerated curing in a vacuum oven, thereby finally obtaining a flexible thermal interface material with phase change function.

[0017] A third aspect of the present invention provides a flexible thermal interface material with phase change function and a preparation method thereof. The thermal interface material is prepared by the above-mentioned preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention uses expanded graphite to adsorb paraffin to prepare phase change particles, and then wraps the phase change particles and aluminum nitride particles with organic silica gel, which effectively improves the thermal conductivity of the material and gives the material a higher melting latent heat value. At the same time, it can effectively inhibit the leakage of paraffin and avoid contaminating electronic devices.

[0020] (2) The present invention uses organic silica gel as the matrix to ensure the good flexibility of the material. After multiple working cycles, there will be no warping phenomenon and it can completely fit the contact surface. When the local temperature of the electronic device gradually increases, the phase change thermal interface material changes from solid to liquid, which can further reduce the heat transfer resistance.

[0021] The present invention provides a flexible thermal interface material with phase change function and a preparation method thereof, which has simple production process, low preparation cost and short production cycle and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The thermal conductivity test results of Examples 1 to 4 of the present invention are shown in FIG.

[0023] Figure 2 The phase change endothermic test results of Examples 1 to 4 of the present invention are shown in FIG. DETAILED DESCRIPTION

[0024] The purpose of the present invention is to provide a flexible thermal interface material with phase change function and a preparation method thereof, so as to solve the problem of low thermal conductivity and lack of phase change absorption of the thermal interface material, and to use phase change particles to increase the melting latent heat value and thermal conductivity of the material.

[0025] The present invention provides a flexible thermal interface material with phase change function and a preparation method thereof, comprising raw materials of various components in parts by mass: 47.5 parts of double-end side chain vinyl silicone oil, 2.5 parts of hydrogen-containing silicone oil, 0.1 parts of a catalyst, 57.5 parts of phase change particles and 0 to 6 parts of aluminum nitride particles.

[0026] The specific embodiments of the present invention will be further explained below with reference to the accompanying drawings and examples.

[0027] The "parts" described in the following examples are all "parts by mass".

[0028] Comparative Example 1

[0029] (1) Weigh 47.5 parts of double-end side chain vinyl silicone oil and 2.5 parts of hydrogen silicone oil into a proportional beaker and stir at 400 r / min for 15 min.

[0030] (2) Add 0.1 parts of platinum catalyst and continue stirring at 400 r / min for 50 seconds.

[0031] (3) Degas the mixture under vacuum at 25°C and -5 kPa for 5 minutes and set it aside after solidification.

[0032] Example 1

[0033] (1) 200 parts of paraffin wax were heated to completely melt at 70°C, 10 parts of expanded graphite were added to the molten paraffin wax liquid, and stirred at a speed of 400 r / min for 3 hours to prepare a composite phase change material block. Furthermore, the composite phase change material block was crushed using a high-speed crusher, and the particles were screened to finally obtain phase change particles with particle sizes of 0.2-0.45 mm, 0.1-0.2 mm, and less than 0.1 mm.

[0034] (2) Pour 30 parts of 0.2-0.45 mm, 17.5 parts of 0.1-0.2 mm, 10 parts of phase change particles smaller than 0.1 mm and 0 parts of aluminum nitride particles into 47.5 parts of double-end side chain vinyl silicone oil and stir for 30 minutes (400 r / min), then continue to add 2.5 parts of hydrogenated silicone oil and stir for 15 minutes (400 r / min).

[0035] (3) Add 0.1 parts of platinum catalyst and continue stirring at 400 r / min for 50 seconds.

[0036] (4) Degas the mixture under vacuum at 25°C and -5 kPa for 5 minutes and set it aside after solidification.

[0037] Example 2

[0038] Other conditions are the same as those in Example 1, except that the amount of synthetic material in this example is changed to 2 portions of aluminum nitride particles.

[0039] Example 3

[0040] Other conditions are the same as those in Example 1, except that the number of synthetic materials in this example is changed to 4 parts of aluminum nitride particles.

[0041] Example 4

[0042] Other conditions are the same as those in Example 1, except that the number of synthetic materials in this example is changed to 6 parts of aluminum nitride particles.

[0043] The thermal conductivity of the materials of Examples 1 to 4 was tested using a thermal constant coefficient analyzer (TPS2500S). The test results are as follows: Figure 1 The test results are summarized in the following table:

[0044] Thermal conductivity (W / m·K) Comparison 1 0.17 Example 1 0.51 Example 2 0.53 Example 3 0.57 Example 4 0.59

[0045] The sample with an initial mass of M0 is placed on filter paper in a constant temperature and humidity chamber maintained at 60°C. The sample is taken out and weighed every hour. The mass of the sample after heating in the constant temperature and humidity chamber for n hours is defined as M n , the material leakage rate calculation formula is as follows:

[0046] S=(M0-M n ) / M0×100%

[0047] The final leakage rates of Experimental Examples 1 and 4 after heating for 100 hours were 3.5% and 1.3%, respectively.

[0048] The melting temperature and melting latent heat of the samples were measured by differential scanning calorimetry (DSC-60plus) in a test temperature range of 20°C to 80°C and a heating rate of 5°C / min.

[0049] According to the above method, the latent heat value and phase change temperature test results of the thermal interface material obtained in Examples 1 to 4 are shown in the following table:

[0050]

[0051]

Claims

1. A flexible thermal interface material with phase change function and a preparation method thereof, characterized in that: The invention comprises the following raw materials in parts by mass: 47.5 parts of double-end side-chain vinyl silicone oil, 2.5 parts of hydrogenated silicone oil, 0.1 parts of catalyst, 57.5 parts of phase change particles and 0 to 6 parts of aluminum nitride particles. The double-end side-chain vinyl silicone oil in parts by mass is weighed and added into a glass beaker, and pre-stirred and dispersed by a high-speed stirrer. Then, the phase change particles and aluminum nitride particles in parts by mass are weighed and added into the double-end side-chain vinyl silicone oil, and stirring is continued for not less than 30 minutes, so that the double-end side-chain vinyl silicone is The mixture of oil, phase change particles and aluminum nitride particles has the function of phase change heat absorption and heat conduction. Secondly, the hydrogen-containing silicone oil is weighed in parts by mass and added to the mixture of double-end side chain vinyl silicone oil, phase change particles and aluminum nitride particles and continued to stir for 15 minutes. Finally, the catalyst is weighed in parts by mass and added to the beaker to promote the addition curing reaction between the double-end side chain vinyl silicone oil and the hydrogen-containing silicone oil in the above mixture. Finally, it is cooled to room temperature to prepare a flexible thermal interface material with phase change function.

2. A flexible thermal interface material with phase change function and a preparation method thereof according to claim 1, characterized in that: The double-end side chain vinyl silicone oil has a viscosity of 500-700 cst, a vinyl content of 10 mol%, and a volatile content of ≤1%.

3. The flexible thermal interface material with phase change function and the preparation method thereof according to claim 1, characterized in that: The phase change particles are prepared by high-temperature melt blending of expanded graphite and paraffin in a ratio of 1:20 by mass into a composite phase change material block; secondly, the composite phase change material block is crushed and the particles are screened using a high-speed crusher, and finally the phase change particles with particle sizes of 0.2-0.45 mm, 0.1-0.2 mm and less than 0.1 mm are obtained, the phase change temperature of the phase change particles is 20-55°C, and the phase change latent heat value of the phase change particles is not less than 207 J / g.

4. The flexible thermal interface material with phase change function and the preparation method thereof according to claim 1, characterized in that: The aluminum nitride particles are hexagonal aluminum nitride particles, wherein the particle size is 1 μm and the specific surface area is 1.5 to 2 m 2 / g.

5. The flexible thermal interface material with phase change function and the preparation method thereof according to claim 1, characterized in that: The steps include: (1) heating paraffin wax at 70° C. until completely melted, heating expanded graphite into the molten paraffin wax, stirring at a speed of 400 r / min for 3 h, cooling to room temperature, and crushing to obtain phase change particles having particle sizes of 0.2 to 0.45 mm, 0.1 to 0.2 mm, and less than 0.1 mm, respectively; (2) adding the phase change particles and aluminum nitride particles of different particle sizes obtained in step (1) to the double-end side chain vinyl silicone oil, wherein the phase change particles include 30 parts of 0.2-0.45 mm, 17.5 parts of 0.1-0.2 mm, and 10 parts of phase change particles less than 0.1 mm, and 0-6 parts of aluminum nitride particles, and stirring them thoroughly for 30 minutes after mixing, and then continuing to add hydrogenated silicone oil and stirring for 15 minutes; (3) adding a platinum catalyst dropwise and continuing stirring for 50 seconds to promote the addition curing reaction; (4) Before the prepared mixture material is completely cured, the mixture is subjected to vacuum degassing and accelerated curing in a vacuum oven, thereby finally obtaining a flexible thermal interface material with phase change function.